Histone acetylation at the sulfotransferase 1a1 gene is associated with its hepatic expression in normal aging. Issue 9 (December 2021) - Kronfol, Mohamad M.; Abudahab, Sara; Dozmorov, Mikhail G.; Jahr, Fay M.; Halquist, Matthew S.; McRae, MaryPeace; Wijesinghe, Dayanjan S.; Price, Elvin T.; Slattum, Patricia W.; McClay, Joseph L.
Abstract : Objectives: Phase II drug metabolism is poorly studied in advanced age and older adults may exhibit significant variability in their expression of phase II enzymes. We hypothesized that age-related changes to epigenetic regulation of genes involved in phase II drug metabolism may contribute to these effects. Methods: We examined published epigenome-wide studies of human blood and identified the SULT1A1 and UGT1A6 genes as the top loci showing epigenetic changes with age. To assess possible functional alterations with age in the liver, we assayed DNA methylation (5mC) and histone acetylation changes around the mouse homologs Sult1a1 and Ugt1a6 in liver tissue from mice aged 4–32 months. Results: Our sample shows a significant loss of 5mC at Sult1a1 (β = −1.08, 95% CI [−1.8, −0.2], SE = 0.38, P = 0.011), mirroring the loss of 5mC with age observed in human blood DNA at the same locus. We also detected increased histone 3 lysine 9 acetylation (H3K9ac) with age at Sult1a1 (β = 0.11, 95% CI [0.002, 0.22], SE = 0.05, P = 0.04), but no change to histone 3 lysine 27 acetylation (H3K27ac). Sult1a1 gene expression is significantly positively associated with H3K9ac levels, accounting for 23% of the variation in expression. We did not detect any significant effects at Ugt1a6 . Conclusions: Sult1a1 expression is under epigenetic influence in normal aging and this influence is more pronounced for H3K9ac than DNA methylation or H3K27ac in this study. More generally, our findings support the relevance of epigenetics in regulating key drug-metabolizing pathways. In the future, epigenetic biomarkers could prove useful to inform dosing in older adults. Abstract : Supplemental Digital Content is available in the text.